Trends in savannah waterbirds: protected area effect and influence of global threats on differing guilds. (2nd April 2020) - Tarakini, Tawanda; Mundy, Peter; Fritz, Hervé
Abstract : Understanding species threats is underpinned by information on their population trends. We investigated the contribution of population drivers associated with 86 waterbird species' trends at a local scale, Hwange National Park (HNP) and a national scale (Zimbabwe). We used logistic regression models to test whether waterbird population trends differed across migration types, seasons, species traits (guild, weight, index of diet variety, social foraging and breeding systems), scale of use by humans (whether the waterbird species utilisation is documented at local or international scale) and susceptibility to hunting and diseases. In HNP during the wet season, waterbird population trends were mostly stable or increasing. During the dry season, larger species were more likely to be recorded, more so for those threatened by hunting, compared with the species limited by diseases. Colonial resident waterbirds had more increasing population trends in HNP in comparison to the solitary ones. At the Zimbabwean scale, records for 35% of species decreased during the wet season, and the declines were more pronounced in large birds. During the dry season, species threatened by habitat disturbances were more likely to decrease. Habitat disturbances and/or use of waterbirds at the international scale are more associated with declining trends than ecological and life history traits. We have shown that HNP, a protected area with mostly a pan wetland-system is supporting growing waterbird populations despite the species facing global negative population trends.